From Empire to Extraction: The Historical Trajectory of Palm Oil Trade and Deforestation in Europe and Indonesia (1800–1945) - Taniwiryono, Darmono (International Journal of Oil Palm, 2025)
Palm oil, a native crop of West Africa, emerged as a key industrial commodity in the 19th century, fundamentally shaping economic and environmental landscapes in both Europe and Southeast Asia. While its importance in European industrialization has been widely acknowledged, the early colonial expansion of oil palm cultivation in Indonesia and its impact on deforestation remains less discussed. This paper explores the intertwined economic, political, and environmental dimensions of palm oil trade in Europe post-1800 and the early plantation-based land conversion in Indonesia before 1945. Drawing on archival sources, historical records, and academic studies, it highlights the dual role of palm oil as both an enabler of industrial progress and a driver of ecological transformation.